2007
DOI: 10.2215/cjn.01820506
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Urinary Tract Infection on Outcomes after Renal Transplantation in Children

Abstract: Urinary tract infection (UTI) is the most common infection after kidney transplantation.A previous analysis showed that late (>6 mo after transplantation) UTI is associated with earlier graft loss in adults. It was hypothesized that children who are younger than 18 yr would be at higher risk to develop UTI and develop graft loss after both early and late UTI. The US Renal Data System database was analyzed from 1996 to 2000 for Medicare claims (composite of inpatient and outpatient) for UTI up to 36 mo after tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
30
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 24 publications
(23 reference statements)
8
30
0
2
Order By: Relevance
“…In our study, as in most others, younger age at transplantation was associated with post-KTx UTI [4,5,15]. Similarly, an age of <5 years persisted as a risk factor for post-KTx UTI and multiple episodes of post-KTx UTI.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In our study, as in most others, younger age at transplantation was associated with post-KTx UTI [4,5,15]. Similarly, an age of <5 years persisted as a risk factor for post-KTx UTI and multiple episodes of post-KTx UTI.…”
Section: Discussionsupporting
confidence: 85%
“…While several studies have reported a rise in serum creatinine during post-KTx UTI, including asymptomatic episodes, reports describing the impact of UTI on long-term graft function have been inconsistent to date [3][4][5][6]. UTI is presumed to impair long-term graft function by predisposing to graft rejection, initially through interstitial inflammation and subsequently through fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Stenosis or leakages would be likely to threaten graft function and need immediate surgical intervention, with likely catastrophic consequences if not corrected. In contrast, an early UTI episode, though potentially graft-threatening in children (17), can often be treated to full resolution by medical means. BKVAN represents a significant risk factor for accelerated graft loss, probably more so than a single UTI episode, but can occur at varying time points after transplant.…”
Section: Discussionmentioning
confidence: 99%
“…These infections may be associated with allograft dysfunction and can predispose patients to the development of acute allograft rejection (11) (12) (13) .…”
Section: Methodsmentioning
confidence: 99%